دراسة تحليليّة بيانية في ديوان الإمام علي بن أبي طالب لعبد الرحمن المصطاوي من ناحية الاستعارة - Dani Yanti, Ana (Journal of Arabic Language and Literature (ALLAIS), 2022)
Sayyidina Ali bin Abi Talib r.a.'s poetry. written and compiled by Abdurrahman al Mushthowi is one of the most famous poems. The poem contains a lot of wisdom and advice, so that many Muslims have quoted the verse and used it as a lesson. However, quite a lot of Muslims do not really understand the meaning contained in these verses, because these verses contain quite a lot of majaz isti'arah. Therefore, with this research, it is hoped that Muslims can better understand the meaning contained in Sayyidina Ali bin Abi Talib r.a's verse. In this study, the researcher focused on two types of isti'arah, namely isti'arah tashrihiyah and makniyyah. The type of research method in this research is qualitative research. After sorting through the documents and data relating to isti'arah tashrihiyyah and makniyyah, the writer then analyzes the data and describes it. The result of this research is that the writer finds 15 stanzas of isti'arah tashrihiyyah, and 22 stanzas of isti'arah makniyyah.